Hubungan Sikap Ibu, Dukungan Keluarga Dan Pola Asuh Dengan Tingkat Kunjungan Anak Balita Usia 12-59 Bulan Ke Posyandu - Gani, Kameriah; Sudarsono, I Made Rai; Hasna, Hasna (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Introduction and Methods Toddlers’ visits to Posyandu (Integrated Health Service Posts) refer to the attendance of children under five years of age to obtain health services such as weight measurement, immunization, and growth and development monitoring. Optimal Posyandu attendance is defined as regular visits conducted once a month during the first five years of life. This study aimed to identify factors associated with the level of toddlers’ visits to Posyandu. This study employed an analytic observational design with a cross-sectional approach and was conducted from February to March 2022 in the working area of Punggaluku Community Health Center, Laeya District, South Konawe Regency. A total of 94 mothers of toddlers were included as respondents, selected using random sampling techniques. Data analysis was performed using the Chi-square statistical test. Results The results showed that most mothers had poor attitudes toward Posyandu attendance (40.4%), insufficient family support (37.2%), and good parenting patterns (7.4%). There was a significant association between maternal attitude and Posyandu visits among toddlers aged 12–59 months (p-value = 0.007), as well as between family support and Posyandu visits (p-value = 0.014). However, no significant association was found between parenting patterns and Posyandu visits among toddlers aged 12–59 months (p-value = 0.759). Conclusion and Recommendations Maternal attitude and family support were significantly associated with Posyandu visits among toddlers aged 12–59 months. Therefore, mothers of toddlers are encouraged to improve their activeness and develop positive attitudes toward Posyandu, as well as to seek and strengthen family support, so that routine and sustainable Posyandu attendance can be achieved. Contribution to the Sustainable Development Goals (SDGs) This study contributes to Sustainable Development Goal (SDG) 3, which aims to ensure healthy lives and promote well-being for all at all ages. Specifically, it supports Target 3.2, which seeks to end preventable deaths of newborns and children under five years of age through the strengthening of basic health services. By identifying factors associated with toddlers’ visits to Posyandu, such as maternal attitude and family support, this study provides evidence to reinforce the role of Posyandu as a community-based health service in monitoring child growth and development. Increased Posyandu attendance is expected to support early detection of nutritional and health problems, thereby contributing to the reduction of morbidity and mortality among toddlers and to sustainable improvements in child health outcomes.